Intracranial migration of intraocular silicone oil mimicking metastatic disease - Nurahmed Mohammed, MD, MS; Daniel Urbine, MD (Radiology Case Reports, 2021)
Silicone oil (SO) is a commonly used agent of intraocular endotamponade for treating complicated retinal detachment. We report a case of SO migration into the cerebral ventricles which was initially misdiagnosed as metastatic disease. Misinterpretation of SO as metastatic disease in a patient with a lung nodule triggered admission to a medical intensive care unit and unnecessary evaluation with further imaging and invasive procedures.